Judicial versus Private Auctions: Better without Protection? - Paredes, Ricardo D.; Crisosto K., Andrés; Martí C., Philippe (Estudios de Economía, 2015)
Using a sample of 680 and 1,300 judicial and private auctions respectively, we analyze the effect on the wealth of those the law is intended to protect of different regulations applicable to each type of auctions. We find that consistent with a simple economic model, Courts assign judicial auctions in a discretional manner, and that the assigned auctioneers charge fees which are substantially higher than those allowed by law. While this behavior put the intended protection to debtor and creditor at risk, economic theory does not rule out a welfare enhancing effect. We test the hypothesis that the judicial auctions’ design reduces the welfare of those intended to protect and, consistent with the predictions of our model, we find it is more likely for Courts to appoint the less effective auctioneers and that the net price received by creditors and debtors in judicial auctions is about 18% to 33% below those that could be obtained in private auctions.